PEMASANGAN REFLEKTOR JALAN DAN SPEED BUMP SEBAGAI UPAYA MENINGKATKAN KESELAMATAN DAN KENYAMANAN DI DESA GONDOWULAN - Refani Abdullah Romadhon; Rifqi Fathul Muhafid; Putri Syavira Farhati; Nur Janah; Muhammad Fahim Lidnillah; Ana Feni Ati; Nila Ni’matul Izza; Atika Nur Safira; Fina Yusriyal Mumtaz; Abdul Mustolif; Puguh Intan Kinasih; Titin Ainur Rohmah; Kholifatur Rofiah; Didi Aditiya Afrizal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Road safety is a crucial aspect that is often overlooked in rural areas, including in Gondowulan Village. Inadequate lighting and the absence of road safety facilities such as road reflectors and speed bumps increase the risk of accidents, particularly at night and in densely populated residential areas. To address this issue, students participating in the Community Service lecture (KPM) implemented a project focused on improving road safety by installing road reflectors and speed bumps at critical points in Gondowulan Village. This activity aimed to enhance nighttime road visibility, reduce vehicle speeds, and raise public awareness about the importance of traffic safety.The project was carried out in several stages: field observations, mapping of accident-prone areas, coordination with village officials, community education, and the technical installation of reflectors and speed bumps through a collaborative effort with local residents. The results showed increased community awareness and a noticeable change in driver behavior—vehicles became slower and more cautious, especially in areas where the safety facilities had been installed.This initiative demonstrates that student involvement through KPM programs can contribute significantly to solving real problems in rural communities. The program not only had a direct impact on road safety but also fostered collaboration between students, local government, and residents in building a safer and more orderly village environment.